(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2012)
This article will explore the concept of focalisation as popularized by Gérard Genette within the field of literature and attempts to apply it to cinematographic studies, more specifically to the 1970s’ popular Italian film genre: giallo. This in order to highlight and clarify certain con- fusions inherent in Genette’s concept, particularly in relation to seeing and knowing. Wishing to dispel this confusion and in pursuit of a more adequate and operational model, we seek not only to review the different gradations of focalisation (zero, internal and external), but also to look at the notions of perception and cognition. Therefore, we find eight possible configura- tions, each liable to produce a different “effect” on the audience. Do we perceive more, less or the same as the characters? Do we know more, less or the same as them? And do we under- stand more, less or the same as them? These are the questions we seek to address, individual- ly and in that order, in an effort to better understand the different effects sought by each of these configurations. We believe that these clarifications will allow for a more grounded model with which to think about cinematic identification.